#Me Too In the Kitchen. (May 2020) - Harris, Deborah A.; Giuffre, Patti
In the wake of the #metoo movement, Harris and Giuffre use the restaurant industry as an example to illustrate how viewing sexual harassment as an issue of industry and organizational culture–rather than just the behavior of a few bad actors–can inform our understanding of sexual harassment in the workplace.